The OPTIMIZATION OF PROFITS AND MANAGEMENT OF RAW MATERIAL STOCKS IN LAUNDRY SOAP MSMES USING INTEGER LINEAR PROGAMMING (ILP) - Eka Pramono, Yuda; Agustina Kurniawati, Dwi; Saif Muhammad Mussafi, Noor (Journal of Industrial Engineering and Halal Industries, 2025)
Abstract Micro, Small, and Medium Enterprises (UMKM) have an important role in the economy, including in the household soap industry. The main problems that are often faced are the management of raw materials and the determination of the amount of production that is not optimal. This study aims to optimize sales profits and the efficiency of the use of raw materials in laundry soap UMKM in Gombong Village, Warungpring District, Pemalang Regency by using the Integer Linear Programming (ILP) method. The data was obtained through direct interviews with UMKM owners and processed using the IBM ILOG CPLEX Optimization Studio. The optimization model is built on two types of products, namely regular soap and soap plus fragrance, taking into account the availability constraints of active ingredients, clean water, liquid fragrances, and plastic bottles. The optimization results showed that the optimal production amount was 47 bottles of regular soap and 53 bottles of soap plus fragrance, with a maximum profit of Rp267,500. This study shows that the ILP method is effective in supporting measurable and efficient production decision-making.